The Description of the Character Education Integration in the Teaching Learning Process at the Tenth Grade of SMA Negeri 1 Gunungsitoli in 2024/2025 - Zalukhu, Saswita; Daeli, Hidayati; Telaumbanua, Yasminar Amaerita; Zega, Riswan (Riwayat: Educational Journal of History and Humanities, 2025)
Character education is an attempt to teach and instill mark favor character, moral, character as development ability somebody so that can take good/bad decisions, exemplary, discipline, and be able to apply it in daily life. Therefore, the objectives of this research were to describe the character education integration in teaching English, to describe the obstacles character education integration in teaching English, and to describe the efforts in character education implementation in teaching English at the tenth grade of SMA Negeri 1 Gunungsitoli in the 2024/2025. The method used in this research was descriptive qualitative. The research data were obtained through observation, questionnaire, and interview which were then analyzed using data analysis technique, namely: data reduction, data display, and conclusion. After analysis, the results indicate that the character education integration in teaching English at the tenth grade of SMA Negeri 1 Gunungsitoli has not been fully realized in the learning process. The findings show that the first teacher in integrate character education in teaching English learning process had integrated 12 character values and 6 character values have been established and the second teacher had integrated 13 character values and 5 character values have been established. Based on the results of interviews done by the researchers, that found out the obstacles faced by the English teacher in integrating character education in teaching learning are Providing a lost-and-found facility, Lost-and-found notice board, Displaying slogans or mottos about hard work and learning, Displaying achievement certificates and awards, Reducing the use of plastic in the classroom.